The Interactive Influence of Perceived Ownership and Perceived Choosership of Stocks on Brain Response to Stock Outcomes - Shang, Zhe; Wang, Lei; Wu, Han (Frontiers in Psychology, 2017)
The present research examined the influence of perceived ownership (self/ other) and perceived chooser (self/ other) of stocks on brain activity, and investigated whether differential brain responses to stock outcomes as a result of perceived differences in ownership of stock would be modulated by perceived chooser of stock. We used a 2 (stock chooser: self, other) × 2 (stock owner: self, other) within-subject design to represent four types of chooser-owner relationships. Brain potentials were recorded while participants observed increasing and decreasing stock prices. Results showed that observations of stock outcomes among four types of chooser-owner relationships elicited differentiated feedback-related negativity (d-FRN: differences in FRN waves between losses and gains, reflecting violations of expectancy to stock outcomes): 1) Self-chosen-other-owned stocks evoked signiﬁcantly larger d-FRN discrepancies than self-chosen-self-owned stocks, indicating a greater expectancy violation to others’ losses than to one’s own, demonstrating a reversed ownership effect. Moreover, people high in conscientiousness showed an increase in this trend, suggesting a stronger other-consideration; 2) Self-chosen-self-owned stocks and other-chosen-self-owned stocks revealed no significant d-FRN discrepancy, showing no choosership effect beyond the ownership effect; 3) Other-chosen-self-owned stocks evoked a signiﬁcantly stronger d-FRN discrepancy than other-chosen-other-owned stocks, demonstrating an ownership effect; 4) Self-chosen-other-owned stocks evoked a signiﬁcantly stronger d-FRN discrepancy than other-chosen-other-owned stocks, revealing a choosership effect. These findings suggest that the ownership effect could be reversed by conscientiousness induced by perceived choosership in the agency relationship, while the choosership effect is attenuated and even disappears under the influence of perceived ownership.